Fluid-Rock Interaction During Hydrothermal Alteration at Parangtritis Geothermal Area, Yogyakarta, Indonesia - Yudiantoro, D. F.; Haty, I. Permata; Sayudi, D. S.; Aji, A. Bayu; C., S. Umiyatun; Adrian, M. Nuky (Geological Agency, 2019)
DOI: 10.17014/ijog.6.1.29-40Parangtritis Volcano is part of the Tertiary magmatic belt in Java, which was tectonically formed by collisions between the Eurasian Continental Plate and Indo-Australian Oceanic Plate. The collisions have taken place since Late Cretaceous and still continue until today. In that period, the magmatic belt in Java Island was formed and produced mineralization and geothermal. The characterization of geothermal in Tertiary volcanoes differs from the geothermal system that is on Quaternary volcano alignment in the middle of Java, such as: Awibengkok, Wayang Windu, Darajat, and Kamojang which have a high temperature. The purpose of this research is to study the mobilization elements due to interaction of hydrothermal fluids with wall rocks in low enthalpy geothermal regions of the Tertiary magmatic arc in Parangtritis. Identification of minerals and chemical element changes is approached by methods of petrographic and scanning electron microscope (SEM) analyses. As for knowing the composition and the origin of hydrothermal fluids, it used analyses of cations, anions, and isotope δ18O and δD of hot water manifestation. The occurrence of geothermal manifestations in Parangtritis, such as hot water and rock alteration, reflects the interaction of hydrothermal fluids with wall rocks which generates an argillic zone with mineral alteration such as quartz, calcite, montmorillonite, and hematite. The presence of alteration mineral montmorillonite replacing pyroxene provides an evidence that there have been interactions between the fluids and rocks. This interaction is as a process of element mobilization. Decrease in elements Si, Ca, Mg, and Fe is accompanied by an increase of Al during the replacement of pyroxene into montmorillonite. The mobility of this element occurs due to acid fluids. However, the hydrothermal fluid composition of the current hot water manifestation is neutral chloride water type composition, and the origin of the fluids is meteoric water (δ18O: -4.20 ‰ and δD: 23.43 ‰).